Study the influence of filling on foaming process of rigid pvc composites - Tahseen A. Saki; A. V. Markov; E. V. Tokareva; E. Yu. Vatskova (Тонкие химические технологии, 2015)
Foaming of rigid PVC composites filled with chalk by azodicarbonamide was studied. Crosslinking PVC and increase in PVC viscosity during filling were found to have the greatest impact on foaming.